(untitled) (Web of Teachers: Inderscience Research, 2025)
The development and implementation of AI-based English language classes for adults require a structured, methodological approach that ensures the effective integration of technology into the learning process. This abstract outline the key stages involved in forming AI-driven English classes tailored for adult learners, focusing on personalized language acquisition. The stages begin with needs analysis, which identifies learners’ specific language requirements and goals. This informs the curriculum design, where AI tools, such as adaptive learning platforms, speech recognition systems, and automated assessments, are integrated to support diverse learning styles and proficiency levels. Pilot testing follows, allowing educators to refine the AI-driven curriculum based on real-world learner feedback and data. Once optimized, the program moves to full-scale implementation, ensuring that AI tools and traditional teaching methods work harmoniously in the classroom. The final stage, ongoing monitoring and evaluation, focuses on tracking learner progress, collecting feedback, and adjusting the AI system to enhance its effectiveness. Additionally, critical considerations such as cultural sensitivity, ethical concerns, and educator training are addressed throughout the process to ensure the AI system is inclusive, accessible, and impactful. This structured approach ensures that AI technologies are effectively utilized to create an engaging, adaptable, and supportive learning environment for adult learners, ultimately improving their language proficiency and overall learning experience.